How to tell stories to children : and some stories to tell - Bryant, Sara Cone, 1873-1956 (Floating Press, 2009)
One might assume that anyone can make up a story on the spot that will hold the attention of a group of children, but in reality, that's not the case. To really capture the imagination of an audience of young people, special attention has to be paid to narrative structure, storytelling conventions, and embellishments. In.